#TITLE_ALTERNATIVE# - PRADIPTAWARDHANA (NIM: 10312021), DIMAZ
Ozone depletion, or better known as the ozone hole, is an atmospheric phenomenon as the ozone concentration in the Earth's stratosphere layer is depleted. The occurrence of the ozone hole phenomenon is not only caused by ODS (Ozone Depleting Substance) resulting from human activity and the Earth's internal natural factors, but also solar flares and high-energy particles from the coronal mass ejection (CME). The ozone hole observed in both poles of the Earth by OSIRIS, GOMOS, and SCIAMACHY satellites when extreme solar flare occurred. The author sought work between the solar flares and the corona mass ejections against the ozone hole area at both poles. Parameters used to perform configuration include: X-ray flux from the X class solar flares and high-energy particles of Halo corona mass ejection. Using the EP-TOMS (Earth Probe-Total Ozone Mapping Spectrometer) satellite image, this study presented the ozone hole area in the 1996-2005 in both poles, i.e. the widespread asymmetry of the ozone hole at both poles where the south pole has a larger ozone hole area, seasonal influence against ozone hole where winter ozone hole is wider, and ozone state when two events Bastille Day Storm on July 14, 2000 and Halloween Day Storm on October 28, 2003. Influence of position of explosion of Sun in the Sun disk affects its impact on the ozone hole. Plasma or high energy particles from the Sun enlarge the area of the ozone hole.